Registration and query of biophysical parameters using the MyocyteDB platform (Research, Society and Development, 2022)
Currently, the research related to the computational modeling of myocytes has been standing out substantially regarding the knowledge of the complex process of cardiac excitation-contraction. In this context, the availability of a data repository of electrophysiological parameters for the development of mathematical models becomes a growing need. The objective of this article is to present the MyocyteDB web platform that's focused on the inclusion and consultation of biophysical parameters and statistical data for computational modeling of the ventricular myocyte. For the development of this platform, cloud computing technologies (Azure) were used. A careful review of the literature in the search for mathematical models of cardiac electrophysiology was carried out on the conductance values of the main ion channels to compose the initial set of data to be inserted into the platform. From the set of collected values available on this platform, it becomes possible to produce statistical data of a descriptive nature, export data in spreadsheet format, and access the dataset via API. It is expected this platform could be a tool capable of helping future modelers in the research and adjustments of biophysical parameters used in the cardiac electrophysiological modeling process. Thus, providing greater dynamics in the search for values of biophysical parameters used in mathematical modeling of myocytes.